Vegetation Structure and Species Composition Along a Canal-Distance Gradient Across Different Peatland Land Use Types - Silviana, Sinta Haryati; Saharjo, Bambang H.; Sutikno, Sigit; Vetrita, Yenni (Bogor Agricultural University, Indonesia, 2026)
Tropical peatlands are critical ecosystems that provide habitat for biodiversity and store large amounts of carbon, yet they are increasingly degraded due to land-use conversion, drainage, and recurrent fires. This study examined vegetation structure and species composition along a canal-distance gradient (10-350 m across three peatland land-use types: rubber plantation, secondary forest, and burned peatland. Vegetation surveys were conducted using 40 nested plots covering four growth strata (trees, poles, saplings/shrubs, and seedlings/herbs). Community structure was analyzed using the Importance Value Index (IVI), Shannon–Wiener diversity index (H′), Margalef’s richness index (DMg), Pielou’s evenness index (E), and Simpson’s dominance index (C). Differences in environmental parameters among land-use types were tested using one-way ANOVA (p<0.05). Secondary forests exhibited the highest species richness and diversity with balanced structural complexity, whereas rubber plantations showed simplified communities dominated by Hevea brasiliensis. Burned peatlands were characterized by pioneer tree species and dense fern understorey, indicating successional arrest. Secondary forests had higher biodiversity than rubber plantations, which in turn had higher biodiversity than burned peatlands. These findings highlight that land-use intensity, canal proximity, and fire history jointly regulate vegetation dynamics in tropical peatlands and highlight the importance of forest conservation, plantation diversification, and restoration through rewetting and enrichment planting.